Novel glass fiber cloth and preparation method thereof

By adopting a multi-component resin system and bisilane collaborative modification technology, combined with a three-stage curing process, the shortcomings in mechanical properties and durability of traditional glass fiber cloth are solved, and the strength, toughness and interface combination performance are significantly improved.

CN119529699AActive Publication Date: 2025-02-28CHONGQING TENWAYS MATERIAL CORP

Patent Information

Application Number
CN202411532556.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-28
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Traditional fiberglass cloths are difficult to meet the needs of high-end applications in terms of mechanical properties and durability, and the interface bonding strength and stability are insufficient, and the curing network is uneven.

Method used

A ternary resin system of bisphenol F-type epoxy resin, 4-epoxypropyloxy-N,N-diglycidyl aniline and epoxidized soybean oil is used, combined with a bisilane collaborative modification system and a three-stage curing process, a multi-layer crosslinking network and a gradient transition interface layer are formed.

Benefits of technology

The excellent comprehensive mechanical properties of glass fiber cloth have been achieved, the tensile strength and elongation at break have been significantly improved, the interface combination performance has been greatly improved, the water resistance and heat resistance have been significantly improved, and the product durability has also been greatly enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of glass fiber cloth, in particular to novel glass fiber cloth and a preparation method thereof.The novel glass fiber cloth comprises a base cloth layer and a functional bonding layer, and the functional bonding layer comprises, by weight, 45-55 parts of bisphenol F epoxy resin; 25 to 35 parts by weight of 2, 4-epoxy propyl oxygen-N, N-diglycidyl aniline; 15-25 parts by weight of epoxidized soybean oil; 20 to 30 parts by weight of methylhexahydrophthalic anhydride; 2-5 parts by weight of 2, 4, 6-tri (dimethylaminomethyl) phenol; 3 to 8 parts by weight of N-aminoethyl piperazine; 0.8 to 1.5 parts by weight of gamma-glycidyl ether oxypropyl trimethoxy silane; the bisphenol F type epoxy resin provides a rigid framework, the polyfunctional group monomer provides a crosslinking point, the flexible chain segment endows the material with necessary toughness, and the bisphenol F type epoxy resin, the polyfunctional group monomer and the flexible chain segment synergistically form an interpenetrating network structure with gradient characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass fiber cloth, and in particular to a novel glass fiber cloth and a preparation method thereof. Background Art

[0002] As an important composite material reinforcement material, glass fiber cloth is widely used in aerospace, electronics, construction engineering and other fields. With the continuous expansion of application fields, the performance requirements of glass fiber cloth are also increasing. At present, the main technical problems of glass fiber cloth are as follows:

[0003] First, traditional glass fiber cloth generally adopts a single epoxy resin system, with a single molecular chain structure and a relatively simple cross-linking network, which makes it difficult for the material to meet high-end application requirements in terms of mechanical properties and durability. Especially in situations where high strength and high toughness are required at the same time, existing technologies often find it difficult to achieve a good performance balance.

[0004] Secondly, the interface bonding between glass fiber and resin matrix has always been a technical difficulty in this field. Due to the poor compatibility of the hydroxyl groups on the surface of glass fiber and the organic resin matrix, the traditional single silane coupling agent modification method is difficult to form a stable chemical bonding interface, especially in harsh service environments, the interface is prone to failure.

[0005] Thirdly, the curing process of existing glass fiber cloth usually adopts a single curing agent and a simple curing process, which leads to uneven cross-linking network and internal stress concentration, affecting the overall performance and service life of the product. Especially in large-sized products, the problem of uneven curing process is more prominent. Summary of the invention

[0006] In view of the above problems, the present invention provides a novel glass fiber cloth and a preparation method thereof.

[0007] The object of the present invention is to provide a novel glass fiber cloth, comprising a base cloth layer and a functional bonding layer, wherein the functional bonding layer is arranged on one side of the base cloth layer, wherein:

[0008] The functional bonding layer comprises the following components in parts by weight:

[0009] 45-55 parts by weight of bisphenol F epoxy resin;

[0010] 25-35 parts by weight of 4-epoxypropyloxy-N,N-diglycidylaniline;

[0011] 15-25 parts by weight of epoxidized soybean oil;

[0012] 20-30 parts by weight of methylhexahydrophthalic anhydride;

[0013] 2-5 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol;

[0014] 3-8 parts by weight of N-aminoethylpiperazine;

[0015] γ-glycidyloxypropyltrimethoxysilane 0.8-1.5 parts by weight;

[0016] Vinyltriethoxysilane 0.5-1.0 parts by weight.

[0017] Specifically, the bisphenol F epoxy

[0018] The epoxy value of the resin is 0.18-0.191, the epoxy value of the epoxidized soybean oil is 0.15-0.17, and the functionality of the 4-epoxypropyloxy-N,N-diglycidylaniline is 4.

[0019] Specifically, the base fabric layer is formed by weaving, disorderly arranging or randomly distributing glass fiber filaments.

[0020] Specifically, the thickness of the functional bonding layer is 20-30 μm.

[0021] Specifically, it further comprises a covering layer, wherein the covering layer is arranged on a side of the functional adhesive layer away from the base fabric layer, and the thickness of the covering layer is 100-180 μm.

[0022] A method for preparing the novel glass fiber cloth comprises the following steps:

[0023] (1) treating the glass fiber with plasma, based on an oxygen / argon mixed gas, at a power of 100-150 W for 30-60 s to obtain a surface-activated glass fiber;

[0024] (2) forming a base fabric layer by weaving, randomly arranging or randomly distributing the surface-activated glass fibers;

[0025] (3) stirring the base resin component at 60-70° C. and at a speed of 300-500 r / min for 20-30 min to obtain a resin mixture;

[0026] (4) stirring the curing agent component at room temperature at a speed of 200-300 r / min for 10-15 min to obtain a curing agent mixture;

[0027] (5) stirring the interfacial modifier component uniformly at room temperature to obtain a modifier mixture;

[0028] (6) The resin mixture, curing agent mixture and modifier mixture are mixed to obtain a functional adhesive layer coating liquid.

[0029] Specifically, the method further comprises the following steps:

[0030] Under the conditions of temperature of 25±2° C. and relative humidity of 45-55%, the functional bonding layer coating liquid is coated on the base fabric layer at a speed of 2-3 m / min and dried for 5-10 minutes.

[0031] Specifically, the method further comprises the following steps:

[0032] At a temperature of 30±2°C and a relative humidity of 40-50%, the second coating is carried out at a speed of 1.5-2.5 m / min and dried for 8-12 minutes.

[0033] Specifically, the second coating is followed by a curing treatment, wherein:

[0034] The pre-curing temperature is 50℃, keep warm for 30min, and the heating rate is 2-3℃ / min;

[0035] Medium temperature curing temperature is 80℃, keep warm for 20min, and the heating rate is 3-4℃ / min;

[0036] The post-curing temperature is 120°C, the temperature is kept for 10 minutes, and the heating rate is 4-5°C / min.

[0037] Specifically, the base fabric layer has a grammage of 100-300 g / m 2 The weight of the glass fiber cloth is 200-500g / m 2 , the thickness of the glass fiber cloth is 80-300 μm.

[0038] Compared with the prior art, the novel glass fiber cloth and its preparation method of the present invention can achieve the following

[0039] Beneficial effects:

[0040] At the molecular design level, the ternary resin system of bisphenol F epoxy resin, 4-epoxypropyloxy-N,N-diglycidylaniline and epoxidized soybean oil was used to achieve the multi-level construction of the cross-linked network through precise regulation of molecular weight, functional group type and content. Among them, bisphenol F epoxy resin provides a rigid skeleton, multifunctional monomers provide cross-linking points, and flexible segments give the material the necessary toughness. The three work together to form an interpenetrating network structure with gradient characteristics.

[0041] In terms of interface design, the present invention innovatively adopts a dual silane synergistic modification system in conjunction with plasma surface activation treatment. γ-glycidyloxypropyltrimethoxysilane undergoes a ring-opening addition reaction with the resin through the epoxy group, while vinyltriethoxysilane provides an unsaturated double bond. The two silanes form a transition layer with a chemical gradient on a molecular scale, significantly improving the interface bonding strength and stability.

[0042] In terms of process innovation, the present invention designs a unique three-stage curing process with a composite curing agent system. Through the precise control of temperature, time and heating rate, the cross-linking reaction is carried out step by step, which effectively reduces the internal stress and improves the uniformity of the cross-linking density. Especially in the pre-curing stage, the lower temperature is conducive to the orderly arrangement of the molecular chains, laying a good foundation for the subsequent high-temperature curing.

[0043] First, the material exhibits excellent comprehensive mechanical properties, with a tensile strength of up to 210MPa and an elongation at break of 5.5%, achieving a good balance between strength and toughness. This is due to the unique network structure formed by the multi-component resin system and the significant synergistic effect between the components.

[0044] Secondly, the interface bonding performance is greatly improved, the interlayer shear strength reaches 55MPa, and the water resistance and heat resistance are significantly improved. Through electron microscopy observation, it is found that a transition layer with uniform thickness and dense structure is formed in the interface area. This special interface structure is an important guarantee for the excellent performance of the material.

[0045] Finally, the product exhibits excellent durability and can maintain stable performance in harsh environments. This is mainly due to the optimized curing process, which forms a uniform cross-linked network structure and significantly improves the service life of the material.

[0046] In summary, the present invention successfully solves the key technical problems existing in traditional glass fiber cloth through the organic combination of molecular design, interface engineering and process innovation, achieves a comprehensive improvement in performance, and provides a new technical solution for the development of related fields. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0048] Example 1 Lightweight and high-strength new glass fiber cloth

[0049] The novel glass fiber cloth of this embodiment is prepared by the following components and methods:

[0050] First, prepare the functional bonding layer components. They include 45 parts by weight of bisphenol F epoxy resin (epoxy value 0.18), 25 parts by weight of 4-epoxypropyloxy-N,N-diglycidylaniline (functionality 4, Tg 145°C), and 15 parts by weight of epoxidized soybean oil (epoxy value 0.15, molecular weight 1000g / mol). Add 20 parts by weight of methylhexahydrophthalic anhydride, 2 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol, 3 parts by weight of N-aminoethylpiperazine, 0.8 parts by weight of γ-glycidyloxypropyltrimethoxysilane, and 0.5 parts by weight of vinyltriethoxysilane.

[0051] The preparation method comprises the following steps:

[0052] Step (1): The glass fiber is treated with plasma using an oxygen / argon mixed gas (volume ratio 80:20), with the power set to 100 W and the treatment time to 30 seconds. Through the plasma treatment, the activity of the glass fiber surface is significantly improved, and the hydroxyl content is increased, providing a good chemical basis for subsequent interface bonding.

[0053] Step (2): The surface activated glass fiber is woven into a sheet having a gram weight of 100 g / m 2 The base fabric layer.

[0054] Step (3): Stir the base resin component at 60°C and 300 r / min for 20 minutes to obtain a uniform resin mixture. This temperature is conducive to reducing the viscosity of the resin and promoting full mixing between the components.

[0055] Step (4): Stir the curing agent component at room temperature at a speed of 200 r / min for 10 minutes to obtain a curing agent mixture. Mild stirring conditions can avoid premature activation of the curing agent.

[0056] Step (5): Gently stir the interfacial modifier component at room temperature until it is uniform to obtain a modifier mixture.

[0057] Step (6): The above mixture is mixed according to the ratio to prepare a functional bonding layer coating liquid. Preferably, the first coating is carried out at a speed of 2 m / min at 25° C. and a relative humidity of 45%, and dried for 5 min. Subsequently, the second coating is carried out at a speed of 1.5 m / min at 30° C. and a relative humidity of 40%, and dried for 8 min. The final thickness of the functional bonding layer is 20 μm.

[0058] The curing process adopts a three-stage method: pre-curing at 50°C for 30 minutes, with a heating rate of 2°C / min; medium-temperature curing at 80°C for 20 minutes, with a heating rate of 3°C / min; post-curing at 120°C for 10 minutes, with a heating rate of 4°C / min. The weight of the obtained glass fiber cloth is 200g / m 2 , with a total thickness of 80μm.

[0059] Example 2 High-tenacity new glass fiber cloth

[0060] The novel glass fiber cloth of this embodiment uses the following components: First, prepare the functional bonding layer components. Among them, 50 parts by weight of bisphenol F epoxy resin (epoxy value 0.185), 30 parts by weight of 4-epoxypropyloxy-N,N-diglycidylaniline (functionality 4, Tg is 150°C), 20 parts by weight of epoxidized soybean oil (epoxy value 0.16, molecular weight 1000g / mol) are added. 25 parts by weight of methyl hexahydrophthalic anhydride, 3.5 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol, 5 parts by weight of N-aminoethylpiperazine, 1.2 parts by weight of γ-glycidyloxypropyltrimethoxysilane, and 0.8 parts by weight of vinyltriethoxysilane are added.

[0061] The preparation method comprises the following steps:

[0062] Step (1): Preferably, plasma treatment is performed using a mixed gas of oxygen / argon (volume ratio 70:30), with a power of 125 W and a treatment time of 45 seconds. The selection of these process parameters can form more active sites on the surface of the glass fiber, which is beneficial to improving the interface bonding strength.

[0063] Step (2): The surface activated glass fiber is randomly arranged to form a 200 g / m 2 The disordered structural design helps to improve the isotropy of the material.

[0064] Step (3): Stir the base resin component at 65° C. and 400 r / min for 25 min. Higher temperature and stirring speed are conducive to the full mixing of the resin system and improve the uniformity of the system.

[0065] Step (4): Stir the curing agent component at a speed of 250 r / min for 12 minutes at room temperature. Moderate stirring conditions can ensure uniform dispersion of the curing agent while avoiding local overheating.

[0066] Step (5): Stir the interface modifier components uniformly at room temperature. The synergistic effect of the bisilane coupling agent can significantly improve the interface bonding performance.

[0067] Step (6): The above mixture is mixed according to the proportion to prepare a functional bonding layer coating liquid. The first coating is carried out at a speed of 2.5 m / min at 25° C. and a relative humidity of 50%, and dried for 7 minutes. Subsequently, the second coating is carried out at a speed of 2 m / min at 30° C. and a relative humidity of 45%, and dried for 10 minutes. The final thickness of the functional bonding layer is 25 μm.

[0068] The curing process adopts a three-stage method: pre-curing at 60°C for 35 minutes, with a heating rate of 2.5°C / min; medium-temperature curing at 90°C for 15 minutes, with a heating rate of 3.5°C / min; post-curing at 120°C for 10 minutes, with a heating rate of 4.5°C / min. The weight of the obtained glass fiber cloth is 350g / m 2 , with a total thickness of 150μm.

[0069] Example 3 High temperature resistant new glass fiber cloth

[0070] The following components are selected in this embodiment: First, the functional bonding layer components are prepared. Among them, 55 parts by weight of bisphenol F epoxy resin (epoxy value 0.191), 35 parts by weight of 4-epoxypropyloxy-N,N-diglycidylaniline (functionality 4, Tg is 155°C), and 25 parts by weight of epoxidized soybean oil (epoxy value 0.17, molecular weight 1000g / mol). 30 parts by weight of methyl hexahydrophthalic anhydride, 5 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol, 8 parts by weight of N-aminoethylpiperazine, 1.5 parts by weight of γ-glycidyloxypropyltrimethoxysilane, and 1.0 parts by weight of vinyltriethoxysilane are added.

[0071] The preparation method comprises the following steps:

[0072] Step (1): plasma treatment was performed using an oxygen / argon mixed gas (volume ratio 60:40), with a power setting of 150 W and a treatment time of 60 s. High power and long treatment time can form more chemical bonding sites on the fiber surface.

[0073] Step (2): The surface activated glass fiber is randomly distributed to form a 300 g / m 2 The base fabric layer.

[0074] Step (3): Stir the base resin component at 70° C. and 500 r / min for 30 min. High temperature and high speed stirring is beneficial to improving the uniformity and stability of the system.

[0075] Step (4): Stir the curing agent component at a speed of 300 r / min for 15 minutes at room temperature.

[0076] Step (5): Stir the interface modifier component thoroughly at room temperature. A higher content of the disilane system can form a denser interface structure.

[0077] Step (6): The above mixture is mixed according to the proportion to prepare a functional bonding layer coating liquid. The first coating is carried out at a speed of 3 m / min at 27° C. and a relative humidity of 55%, and dried for 10 minutes. Subsequently, the second coating is carried out at a speed of 2.5 m / min at 32° C. and a relative humidity of 50%, and dried for 12 minutes. The final thickness of the functional bonding layer is 30 μm.

[0078] The curing process adopts a three-stage method: pre-curing at 70°C for 40 minutes, with a heating rate of 3°C / min; medium-temperature curing at 100°C for 10 minutes, with a heating rate of 4°C / min; post-curing at 120°C for 10 minutes, with a heating rate of 5°C / min. The weight of the obtained glass fiber cloth is 500g / m 2 , with a total thickness of 300μm.

[0079] Example 4 Lightweight and highly flexible new glass fiber cloth

[0080] The following components are selected in this embodiment: First, the functional bonding layer components are prepared. Among them, 47 parts by weight of bisphenol F epoxy resin (epoxy value 0.188), 28 parts by weight of 4-epoxypropyloxy-N,N-diglycidylaniline (functionality 4, Tg is 148°C), and 18 parts by weight of epoxidized soybean oil (epoxy value 0.16, molecular weight 1000g / mol). 23 parts by weight of methyl hexahydrophthalic anhydride, 3 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol, 6 parts by weight of N-aminoethylpiperazine, 1.0 parts by weight of γ-glycidyloxypropyltrimethoxysilane, and 0.7 parts by weight of vinyltriethoxysilane are added.

[0081] The preparation method comprises the following steps:

[0082] Step (1): plasma treatment was performed using an oxygen / argon mixed gas (volume ratio 75:25) with a power of 135 W and a treatment time of 40 s.

[0083] Step (2): The surface activated glass fiber is woven into a material having a gram weight of 150 g / m 2 The base fabric layer.

[0084] Step (3): Stir the base resin component at 68°C and 450 r / min for 23 minutes.

[0085] Step (4): Stir the curing agent component at a speed of 275 r / min for 13 min at room temperature.

[0086] Step (5): Stir the interfacial modifier component uniformly at room temperature.

[0087] Step (6): The above mixture is mixed according to the proportion to prepare a functional bonding layer coating liquid. The first coating is carried out at a speed of 2.8 m / min at 26° C. and a relative humidity of 48%, and dried for 8 minutes. Subsequently, the second coating is carried out at a speed of 2.2 m / min at 31° C. and a relative humidity of 43%, and dried for 11 minutes. The final thickness of the functional bonding layer is 28 μm.

[0088] The curing process adopts a three-stage method: pre-curing at 65°C for 38 minutes, with a heating rate of 2.8°C / min; medium-temperature curing at 95°C for 18 minutes, with a heating rate of 3.8°C / min; post-curing at 120°C for 10 minutes, with a heating rate of 4.8°C / min. The weight of the obtained glass fiber cloth is 300g / m 2 , with a total thickness of 200 μm.

[0089] The above four embodiments fully demonstrate the feasibility scope of the present invention through different component ratios and process parameters, and verify the synergistic effect of various technical features.

[0090] Comparative Example 1 Single Resin System Glass Fiber Cloth (Comparative Example 1)

[0091] This comparative example uses a single bisphenol F epoxy resin of 85 parts by weight (epoxy value 0.18), without adding 4-epoxypropyloxy-N,N-diglycidylaniline and epoxidized soybean oil. The other components are the same as those in Example 1. The necessity of a multi-resin synergistic system can be verified through this comparative example. A single resin system results in a single cross-linked network structure and lacks the synergistic effect of a multi-level cross-linked network, and the toughness and heat resistance of the final product are significantly reduced. The preparation method is the same as that in Example 1, and the obtained glass fiber cloth exhibits obvious brittleness, and the elongation at break is only 60% of that in Example 1.

[0092] Comparative Example 2 Glass Fiber Cloth without Interface Coupling Agent (Comparative Example 2)

[0093] In this comparative example, γ-glycidyloxypropyltrimethoxysilane and vinyltriethoxysilane were removed, and the proportion of other components was consistent with that of Example 2. The preparation process was the same as that of Example 2, but due to the lack of interfacial coupling, the interfacial bonding strength between the resin matrix and the glass fiber was significantly reduced. The test results showed that the interlaminar shear strength was only 45% of that of Example 2, and the strength retention rate after boiling was reduced to 65%, which fully demonstrated the key role of the double silane synergistic modification system in interfacial performance.

[0094] Comparative Example 3: Glass fiber cloth not treated with plasma (Comparative Example 3)

[0095] This comparative example uses the same formula as Example 3, but omits the plasma treatment step. The results show that the interface bonding between the glass fiber and the resin matrix without surface activation is poor, resulting in a decrease in the overall performance of the composite material. The tensile strength is only 70% of that in Example 3, and the strength retention rate after thermal aging drops to 75%, which fully verifies the importance of plasma treatment in improving the interface bonding strength.

[0096] Comparative Example 4 Curing agent single system glass fiber cloth (Comparative Example 2)

[0097] This comparative example uses only 28 parts by weight of methyl hexahydrophthalic anhydride as a curing agent, removes 2,4,6-tris(dimethylaminomethyl)phenol and N-aminoethylpiperazine, and the other components are the same as those in Example 2. Due to the lack of a synergistic curing system, the crosslinking reaction is incomplete and the cured network structure is not dense enough. The test results show that the glass transition temperature is reduced by 25°C and the heat resistance is significantly reduced.

[0098] Comparative Example 5 Non-optimized curing process glass fiber cloth (Comparative Example 4)

[0099] This comparative example uses the same formula as Example 4, but simplifies the curing process to a single curing step: directly curing at 120°C for 60 minutes. The results show that the failure to adopt a three-stage curing process leads to internal stress concentration in the material and micro cracks. The bending strength is only 65% ​​of that in Example 4, and obvious delamination is shown in the thermal cycle test. This verifies the important influence of the staged curing process on product performance.

[0100] Comparative Example 6 Glass Fiber Cloth with Unbalanced Resin Ratio (Comparative Example 3)

[0101] The resin ratio of this comparative example is adjusted: bisphenol F epoxy resin is increased to 70 parts by weight, 4-epoxypropyloxy-N,N-diglycidylaniline is reduced to 15 parts by weight, and epoxidized soybean oil is reduced to 15 parts by weight. The other components and processes are the same as those of Example 3. Due to the imbalance of the resin ratio and the excessive rigid components, the product toughness is insufficient. The elongation at break is reduced by 45%, and the impact strength is only 55% of that of Example 3. This fully illustrates the necessity of optimizing the resin system ratio.

[0102] Through the above six comparative examples, the system verifies the three core innovations of the present invention:

[0103] 1. Necessity of multi-resin synergistic system (Comparative Examples 1 and 6)

[0104] 2. The key role of the interface modification system (Comparative Examples 2 and 3)

[0105] 3. Importance of process parameter optimization (Comparative Examples 4 and 5)

[0106] These comparative examples verify the necessity and synergistic effect of the various technical features of the present invention from different perspectives, and fully demonstrate the creativity of the present invention. Through the systematic comparison of material properties, the significant advantages of the present invention in terms of mechanical properties, interface properties and durability are clearly demonstrated.

[0107] The present invention comprehensively evaluates the performance of glass fiber cloth according to standard test methods. All tests are conducted under standard laboratory conditions (23±2°C, relative humidity 50±5%), and each set of data is the average value of 5 parallel samples.

[0108] 1. Mechanical properties test

[0109] First, the tensile performance test was carried out according to GB / T1447-2005, using a universal testing machine, the sample size was 250mm×25mm, and the tensile rate was 10mm / min. Secondly, the bending performance was tested according to GB / T1449-2005, using the three-point bending method, the support span was 160mm, and the loading rate was 2mm / min. Thirdly, the impact strength was tested according to GB / T1043.1-2008, using the simply supported beam impact method, and the sample was not notched.

[0110] 2. Interface performance characterization

[0111] The interface structure was observed by scanning electron microscopy (SEM), and the samples were treated with gold spraying after liquid nitrogen brittle fracture. The interlaminar shear strength was tested according to ASTMD2344 standard, and the sample size was 25mm×6mm. Dynamic thermal mechanical analysis (DMA) was further used to test the interface bonding condition, with a heating rate of 3℃ / min and a frequency of 1Hz.

[0112] 3. Durability assessment

[0113] The water resistance test refers to GB / T1034-2008, and the mechanical properties are tested after immersion in 98℃ water for 2h. The thermal aging performance is tested according to GB / T1634-2004, and the residual strength is tested after aging at 150℃ for 24h. In addition, a thermal cycle test from -40℃ to 80℃ was carried out for a total of 50 cycles.

[0114] 4. Microstructure Analysis

[0115] The degree of crosslinking was analyzed by differential scanning calorimetry (DSC) at a heating rate of 10°C / min. The chemical structure was characterized by infrared spectroscopy (FTIR) with a scanning range of 400-4000cm-1. The thermal stability was evaluated by dynamic thermogravimetric analysis (TGA) at a heating rate of 20°C / min.

[0116] The test results are shown in the following table:

[0117] Table 1 Mechanical properties test results

[0118] [Table content includes: sample number, tensile strength (MPa), elongation at break (%), flexural strength (MPa), impact strength (kJ / m 2 )]

[0119] sample Tensile Strength Elongation at break Bending Strength Impact strength Example 1 182 4.8 205 52 Example 2 195 5.2 218 58 Example 3 210 4.5 235 61 Example 4 188 5.5 212 55 Comparative Example 1 125 2.9 145 32 Comparative Example 2 140 3.8 160 38 Comparative Example 3 147 3.2 165 43 Comparative Example 4 135 3.5 155 35 Comparative Example 5 142 3.1 138 37 Comparative Example 6 152 2.5 172 34

[0120] Table 2 Interface performance and durability test results

[0121] [Table contents include: sample number, interlaminar shear strength (MPa), strength retention rate after boiling (%), strength retention rate after heat aging (%), interface bonding index]

[0122] sample Shear Strength Boil retention rate Heat aging retention rate Binding index Example 1 48 88 92 0.92 Example 2 52 91 94 0.95 Example 3 55 93 95 0.98 Example 4 50 90 93 0.94 Comparative Example 1 28 65 70 0.65 Comparative Example 2 25 58 65 0.58 Comparative Example 3 30 62 68 0.62 Comparative Example 4 32 68 72 0.70 Comparative Example 5 35 70 75 0.72 Comparative Example 6 33 65 70 0.68

[0123] According to the test results, the present invention achieves the following unexpected technical effects:

[0124] First, in terms of mechanical properties, Example 3 performs best, with a tensile strength of 210 MPa, which is 68% higher than that of Comparative Example 1. This significant improvement is due to the interpenetrating network structure formed by the synergistic formation of multiple resins. DSC analysis shows that the crosslinking density of the multi-component system is 45% higher than that of the single resin system, and the crosslinking network is more uniform.

[0125] Secondly, the interface performance is outstanding. The interlaminar shear strength of Example 3 reaches 55MPa, which is 2.2 times that of Comparative Example 2. SEM observation shows that the present invention forms a clear gradient transition interface layer with a thickness of about 0.5-0.8μm. This special interface structure originates from the synergistic modification mechanism of double silane. The FTIR spectrum confirms that the silane molecules form chemical bonds with both the matrix and the fiber surface.

[0126] Again, the durability is excellent, and the strength retention rate of Examples 2-4 after boiling is more than 90%, which is much higher than 58-70% of the comparative example. This is due to the dense cross-linked network structure and strong interface bonding. TGA analysis shows that the initial decomposition temperature of the present invention is 35°C higher than that of the comparative sample.

[0127] Finally, a unique phenomenon was found through DMA analysis: the glass transition peak of the present invention showed a double peak feature, which indicated that a true interpenetrating network structure was formed, rather than a simple physical blend. This special structure endowed the material with excellent comprehensive properties.

[0128] Example 3 is the best implementation scheme of the present invention, and its comprehensive performance index is the best, which is due to the synergistic effects of the following aspects:

[0129] 1. The resin ratio is optimal, achieving a balance between rigidity and toughness;

[0130] 2. The curing process parameters are precisely controlled to form an ideal network structure;

[0131] 3. The interface modification effect is the best, and a strong interface bond is established.

[0132] These in-depth experimental data fully confirm the innovation and superiority of the present invention, and also provide reliable technical support for subsequent industrial applications.

[0133] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A new type of glass fiber cloth, characterized in that: It comprises a base fabric layer and a functional bonding layer, wherein the functional bonding layer is arranged on one side of the base fabric layer, wherein: The functional bonding layer comprises the following components in parts by weight: 45-55 parts by weight of bisphenol F epoxy resin; 25-35 parts by weight of 4-epoxypropyloxy-N,N-diglycidylaniline; 15-25 parts by weight of epoxidized soybean oil; 20-30 parts by weight of methylhexahydrophthalic anhydride; 2-5 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol; 3-8 parts by weight of N-aminoethylpiperazine; γ-glycidyloxypropyltrimethoxysilane 0.8-1.5 parts by weight; Vinyltriethoxysilane 0.5-1.0 parts by weight.

2. The novel glass fiber cloth according to claim 1 is characterized in that: The epoxy value of the bisphenol F epoxy resin is 0.18-0.191, the epoxy value of the epoxidized soybean oil is 0.15-0.17, and the functionality of the 4-epoxypropyloxy-N,N-diglycidylaniline is 4.

3. The novel glass fiber cloth according to claim 1 is characterized in that: The base fabric layer is formed by weaving, disorderly arranging or randomly distributing glass fiber filaments.

4. The novel glass fiber cloth according to claim 1, characterized in that: The thickness of the functional bonding layer is 20-30 μm.

5. The novel glass fiber cloth according to claim 1, characterized in that: The invention further comprises a covering layer, wherein the covering layer is arranged on a side of the functional bonding layer away from the base fabric layer, and the thickness of the covering layer is 100-180 μm.

6. A method for preparing the novel glass fiber cloth according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) treating the glass fiber with plasma, based on an oxygen / argon mixed gas, at a power of 100-150 W for 30-60 s to obtain a surface-activated glass fiber; (2) forming a base fabric layer by weaving, randomly arranging or randomly distributing the surface-activated glass fibers; (3) stirring the base resin component at 60-70° C. and at a speed of 300-500 r / min for 20-30 min to obtain a resin mixture; (4) stirring the curing agent component at room temperature at a speed of 200-300 r / min for 10-15 min to obtain a curing agent mixture; (5) stirring the interfacial modifier component uniformly at room temperature to obtain a modifier mixture; (6) The resin mixture, curing agent mixture and modifier mixture are mixed to obtain a functional adhesive layer coating liquid.

7. The preparation method according to claim 6, characterized in that: Further comprising the steps of: Under the conditions of temperature of 25±2° C. and relative humidity of 45-55%, the functional bonding layer coating liquid is coated on the base fabric layer at a speed of 2-3 m / min and dried for 5-10 minutes.

8. The preparation method according to claim 7, characterized in that: Further comprising the steps of: At a temperature of 30±2°C and a relative humidity of 40-50%, the second coating is carried out at a speed of 1.5-2.5 m / min and dried for 8-12 minutes.

9. The preparation method according to claim 8, characterized in that: The second coating is followed by a curing process, wherein: The pre-curing temperature is 50℃, keep warm for 30min, and the heating rate is 2-3℃ / min; Medium temperature curing temperature is 80℃, keep warm for 20min, and the heating rate is 3-4℃ / min; The post-curing temperature is 120°C, the temperature is kept for 10 minutes, and the heating rate is 4-5°C / min.

10. The preparation method according to claim 6, characterized in that: The base fabric layer has a grammage of 100-300 g / m 2 The weight of the glass fiber cloth is 200-500g / m 2 , the thickness of the glass fiber cloth is 80-300 μm.

Citation Information

Patent Citations

  • Prepreg and carbon fiber reinforced composite material

    CN104684975A

  • Modified epoxy resin and glass fiber reinforcement plate prepared based on same

    CN107033328A

  • Epoxy-resin-based polymer material and preparation method and application thereof

    CN112442256A

  • Adhesive for resin roll assembly and resin roll

    CN1437644A

  • Prepreg and carbon fiber-reinforced composite material

    JP2014122312A

Cited By

  • Resin composition, method for preparing glass fiber prepreg and application of glass fiber prepreg

    CN121471660A